IZIN PERKAWINAN DAN PERCERAIAN BAGI PNS (Suatu Analisis Hukum Islam terhadap PP No.10/1983 - Jo PP 45/1990 - Jamil, Jamal (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2014)
The situation and living of the household servants is one of the factors important role in efforts to help improve service tasks, then the life of civil servants must be supported by a harmonious family life, so that the execution of his duty not to be disturbed by family problems. Therefore issued PP. No10 of 1983-jo PP 45/1990 on Marriage License and Percerailan for civil servants. Government regulation is substantially more difficult for civil servants to be polygamous and will do divorce than the UUP. And forbids civil servants to live together outside marriage. With the release of PP. was, civil servants who will perform polygamous marriage and divorce must obtain permission from officials. The requirement of a permit from government officials was intended to prevent the occurrence of polygamy and divorce.